The Use of Jarimatics as a Media in Learning Calculating at Elementary School - Arini Ulfa Mawaddah; Nurjannah Nurjannah; Andi Baso Kaswar (Pengabdian: Jurnal Abdimas, 2024)
Jarimatics is a way of calculating mathematics for children using the fingers developed due to the difficulty of students counting using all the fingers and toes. The use of these jarimatics aims to facilitate students in learning to count. Using jarimatics can increase students' interest and enthusiasm for learning to count. This study has several obstacles because some students still need help understanding multiplication. Direct practicum methods and lecture methods carry out this implementation method. The training participants were 18 grade 2 students. This coaching occurred in a class 2 at SD Negeri 276 Lemo. Based on the coaching carried out, the desired results are well achieved. Namely, students become more enthusiastic and easy to understand in learning to count. Students become more eager to learn and faster in the calculation process. Therefore, it can be concluded that this training positively impacts students' mathematics learning.